Author response: Incident parkinsonism in older adults without Parkinson disease. (28th February 2017) - Buchman, Aron S.; Bennett, David A.
Abstract : We thank Mahlknecht et al. for the interest in our study, which reported on risk factors for incident parkinsonism in community-dwelling older adults without Parkinson disease (PD). 1 Mahlknecht et al. confirmed and extended some of our findings, growing the literature that demonstrates that PD, like other chronic diseases of aging, has a long subclinical phase in which brain pathology develops without clinical signs or symptoms, followed by mild signs and symptoms of insufficient severity to warrant a diagnosis of PD, with PD representing a late manifestation. 2 Overall, this conceptual model is similar to the one currently used for Alzheimer disease (AD). 3 However, parkinsonian signs are much more common than subclinical PD pathology and are associated with diverse brain pathologies. 4, 5 Thus, like AD dementia, the clinical phenotype of parkinsonism in older adults may be caused by diverse etiologies. A means for identifying the subset of persons with parkinsonian signs who have PD pathology and are therefore likely to be at a higher risk for progressing to PD is urgently needed.